2019
DOI: 10.1097/aln.0000000000002528
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function in Astrocytes Is Essential for Normal Emergence from Anesthesia in Mice

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background In mice, restriction of loss of the mitochondrial complex I gene Ndufs4 to glutamatergic neurons confers a profound hypersensitivity to volatile anesthetics similar to that seen with global genetic knockout of Ndufs4. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…The strength of this study is that different agents were used and showed similar effects on brain lactate release and astrocytic glycolysis. Our experiments focused on the glycolytic aspect of brain energy metabolism and more specifically on the supply of lactate by astrocytes to support the metabolic needs of active neurons, which compliment recently published works in the field ( Ramadasan-Nair et al, 2019 ). In addition, changes in brain lactate release under anaesthesia and sleep have been comparatively assessed.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The strength of this study is that different agents were used and showed similar effects on brain lactate release and astrocytic glycolysis. Our experiments focused on the glycolytic aspect of brain energy metabolism and more specifically on the supply of lactate by astrocytes to support the metabolic needs of active neurons, which compliment recently published works in the field ( Ramadasan-Nair et al, 2019 ). In addition, changes in brain lactate release under anaesthesia and sleep have been comparatively assessed.…”
Section: Discussionmentioning
confidence: 77%
“…Lactate is supplied to neurons by neighbouring astrocytes following glycolytic breakdown of glucose and release via monocarboxylate transporters (MCTs) ( Perez-Escuredo et al, 2016 ) and/or certain membrane channels ( Sotelo-Hitschfeld et al, 2015 ; Karagiannis et al, 2016 ; Hadjihambi et al, 2017 ). There is evidence that reduced glucose metabolism in astrocytes delays emergence from general anaesthesia ( Ramadasan-Nair et al, 2019 ). However, the effects of general anaesthesia on brain energy metabolism are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, our previous work has shown the importance of neuron-astrocyte crosstalk in the development of neurodegeneration in the context of mitochondrial disease (Liu et al, 2015). However, astrocytic Ndufs4 deficiency is not sufficient to recapitulate the phenotype of global Ndufs4KO mice (Ramadasan-Nair et al, 2019), underscoring the central role of neurons in the disease. Even so, recent studies have shown enhanced neuronal survival in global Ndufs4KO after disruption of hepatic S6K1 (Ito et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These drugs are clinically classified as inhaled or injectable, and then by what are thought to be the principle molecular targets (e.g., glutamatergic or GABAergic), although many targets likely contribute 2 . Targets include a wide range of voltage and ligand gated ion channels, transporters, second messenger and mitochondrial proteins 3 , 4 , with the injectable drugs being somewhat more selective 5 8 .…”
Section: Introductionmentioning
confidence: 99%